Advances in virus research. - Maramorosch, Karl; Murphy, Frederick A.; Shatkin, Aaron J. (Advances in virus research ;, 1996)
Praise for the Series: "This serial ... is well known to virologists. It is a valuable aid in maintaining an overview of various facets of the rapidly expanding fields of virology ... Timely, informative, and useful to student, teacher, and research scientist."--American Scientist "A mandatory purchase for all types of comprehensive libraries, both public and university, as well as for those interested in or doing research in the field of virology."--Military Medicine Key Features * Among the topics covered are: * Virus-induced immunopathology * Filoviruses * Molecular characterization of pestiviruses * Transactivation of cellular genes by hepatitus B virus proteins * Principles of molecular organization, expression, and evolution of closteroviruses * Primate T lymphotropic oncoretroviruses * Replication of positive-stranded RNA viruses of plants and animals